Impact of inpatient self-efficacy and trust in physicians on inpatient satisfaction with medical services: the mediating role of patient participation in medical decision-making - Wang, Haixia; Jia, Jie; Fan, Yafeng; Chen, Hanlin; Lou, Yi; Wang, Xiaohe; Huang, Xianhong (Frontiers in Psychology, 2024)
Objective Patient satisfaction reflects the social benefits of hospitals and is an important indicator of hospital performance. This study explores the mechanism through which inpatients’ trust in physicians, self-efficacy, and participation in medical decision-making impact their satisfaction with medical services. Methods A questionnaire was administered to 814 inpatients in 10 randomly selected tertiary hospitals and 10 randomly selected secondary hospitals in Hangzhou, China. A correlation analysis and hierarchical linear regression were conducted to analyze the factors influencing inpatient satisfaction. Results The outcome measures of trust in physicians and participation in medical decision-making behaviors had significant positive effects on inpatient satisfaction. Trust in physicians was shown to directly influence inpatient satisfaction, while inpatient participation in decision-making partially mediated this relationship. Inpatient participation in medical decision-making fully mediated the relationship between self-efficacy and inpatient satisfaction. Conclusion While inpatients were relatively satisfied, there is room for improvement. Healthcare providers should improve patient trust by actively listening to their needs and providing feedback, establishing effective communication mechanisms. Patient self-efficacy can be enhanced through health education, special lectures, and case sharing. Patients should also be encouraged to actively participate in medical decision-making. Practical implications Based on inpatient feedback during a preliminary survey, we refined this study’s questionnaire to enhance its feasibility for future research. This article shares key findings for healthcare managers and providers, advising that patient satisfaction can be enhanced through trust, self-efficacy, and participation.